Identifikasi Parasit Pada Ikan Mujair (Oreochromis Mossambicus) Di Daerah Taman Pancing Denpasar Selatan - Rasmi, Kadek Anidia; Dewi, Ade Ayu Yasinta; Artini, Ni Putu Rahayu (Bali International Scientific Forum, 2020)
Background : One of the most dangerous diseases for tilapia fish is parasites. This certainly can cause a decrease in fish quality and health problems in humans. Objective: This study aims to identify the type of parasite that infects tilapia fish (Oreochromis mossambicus) in the Fishing Park area of ​​South Denpasar District. Methods: A total of 26 tilapia fish taken from the Fishing Park area were examined at the Microbiology Laboratory of the University of Bali International to see the presence of ectoparasites and endoparasites. Ectoparasites are examined by observing external organs and then examined under a microscope, while endoparasites are examined by observing the inner surface of the digestive tract. Results: From the results of the study found two types of parasites that infested tilapia fish in the Fishing Park area namely Ascaris sp. and Ancylostoma sp. As many as 53.8% of tilapia fish were infested with Ascaris sp., And 46.2% were infested with Ancylostoma sp. The intensity of Ascaris sp. as many as 2 individuals / tail and Ancylostoma sp. as many as 1 individual / tail. Conclusion: Based on the results of observations made, it is known that from 26 tilapia fish obtained in Taman Pancing in the South Denpasar District, all fish samples were infected with parasites. This indicates that tilapia fish in the area are not suitable for consumption because they can transmit parasites through the fecal-oral route.